Contrast-Enhanced Ultrasound (CEUS) in Non-Traumatic Abdominal Emergencies - Cozzi, Diletta; Agostini, Simone; Bertelli, Elena; Galluzzo, Michele; Papa, Emanuela; Scevola, Germano; Trinci, Margherita; Miele, Vittorio (Ultrasound International Open, 2020)
Conventional ultrasound imaging (US) is the first-line investigation in acute non-traumatic abdominal emergencies, but sometimes it needs further examinations, such as computed tomography (CT), to reach a certain diagnosis. Contrast-enhanced ultrasound (CEUS), through injection of contrast medium, may provide the radiologist with additional information that could not be investigated with baseline US. It could help reach a diagnosis and rapidly determine the proper therapy in an emergency setting. The purpose of this review is to explain and illustrate the various possibilities and limitations of CEUS in acute non-traumatic abdominal diseases, in particular acute inflammation, parenchymal infarcts, and hemorrhages.
Keywords: ultrasound; CT; acute; abdomen